Analysis of hemodynamics, prognostic parameters and dietary habits in subjects with aortic stenosis and increased risk of patient-prosthesis mismatch - Pińska, Małgorzata (2024)
The KRAK-AS registry was conducted from July to October 2016 and aimed to evaluate patients diagnosed with at least moderate aortic stenosis (AS). Patients were evaluated clinically and echocardiographically before and after aortic valve surgery. A dietary interview based on the KomPAN questionnaire was also conducted. The endpoint of the study was death from any cause after 3 years of follow-up from the date of inclusion in the study. The course of diagnosis and treatment of the patient diagnosed with Heyde syndrome was analyzed. Conclusions: Moderate patient-prosthesis mismatch (PPM) is common after surgical aortic valve replacement, but much rarer with the transcatheter TAVI procedure. Severe PPM is rare, occurring in 2.6%. Dietary habits and nutritional knowledge in patients with AS are inadequate. Proper dietary education is necessary in all patients with aortic valve stenosis. The size and volume of the left atrium and the presence of atrial fibrillation are important risk factors for death in patients with AS. The presence of renal dysfunction, low left ventricular ejection fraction, high NYHA functional class and atrial fibrillation are additional risk factors for poor prognosis in patients with AS. Hyde syndrome should be considered in patients with AS and concurrent gastrointestinal bleeding.
Keywords: aortic stenosis; echocardiography; atrial fibrillation; Heyde syndrome; patient-prothesis mismatch